2007
DOI: 10.1007/s11605-007-0174-3
|View full text |Cite|
|
Sign up to set email alerts
|

The Pathogenesis of Barrett’s Esophagus: Secondary Bile Acids Upregulate Intestinal Differentiation Factor CDX2 Expression in Esophageal Cells

Abstract: These findings show that secondary bile acid stimulation upregulates CDX2 gene expression in both normal and cancer cell lines. They further support the role of bile acids in the pathogenesis of Barrett's esophagus and link the clinical evidence of a high prevalence of luminal bile acids in Barrett's to expression of the gene thought to be responsible for the phenotypic expression of intestinal metaplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 16 publications
3
42
0
1
Order By: Relevance
“…These markers are also increased in BE metaplasia (19,38). Furthermore, these results are in agreement with recent studies, indicating that bile acids at low pH may induce an increase in the expression of CDX2, CK8/18, and villin in other model systems (5,6,13,24,25,66). At this point, it is not clear why we did not observe an increase in CDX2 mRNA, while villin mRNA was significantly increased.…”
Section: G298 Resistance To Bile Acids and Acid In Esophageal Cellssupporting
confidence: 88%
“…These markers are also increased in BE metaplasia (19,38). Furthermore, these results are in agreement with recent studies, indicating that bile acids at low pH may induce an increase in the expression of CDX2, CK8/18, and villin in other model systems (5,6,13,24,25,66). At this point, it is not clear why we did not observe an increase in CDX2 mRNA, while villin mRNA was significantly increased.…”
Section: G298 Resistance To Bile Acids and Acid In Esophageal Cellssupporting
confidence: 88%
“…[26][27][28] In previous studies, DCA showed the strongest effect on Cdx2 transcription of all bile acids. [29][30][31] In our earlier reports, we proposed that bile acids suppress the expression of Hes1 via Cdx2 activation in esophageal epithelial cells, with resulting activation of ATOH1 and MUC2. 3,13 In the present study, Dll1 expression was upregulated in Het-1A, CP-A and BAR-T cells by exposure to DCA.…”
Section: Discussionmentioning
confidence: 99%
“…Cdx2 is reported to be expressed in Barrett's epithelium and a number of studies have found that it is a key mediator in the development of Barrett's esophagus. 11,21,25,35 Previously, we showed that bile acids activated the Cdx2 promoter via NF-kB and stimulated the production of Cdx2 protein in esophageal keratinocytes, which is an important step in the development of Barrett's epithelium. 13 In addition to Cdx2, ATOH1 is also reported to be expressed in Barrett's metaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Incubation time, DCA, CA, DAPT, and concentrations were chosen according to the criteria described elsewhere. 18,[25][26][27] RNA Extraction and Complementary DNA (cDNA) Syntheses Total RNA was extracted using a single-step guanidium thiocyanate-phenol-chloroform method (Isogen; Nippon Gene, Tokyo, Japan), according to the manufacturer's instructions. Total RNA concentrations were determined by spectrophotometric quantification at 260 nm using Nanodrop (type ND-1000; NanoDrop Technologies, Wilmington, DE, USA) and the integrity of the bands was verified visually by agarose gel electrophoresis.…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%